2021
DOI: 10.1007/s11136-021-02984-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CNS-directed treatment on quality of life in childhood cancer survivors

Abstract: Purpose Pediatric cancer survivors may have lower quality of life (QoL), but most research has assessed outcomes either in treatment or long-term survivorship. We focused on early survivorship (i.e., 3 and 5 years post-diagnosis), examining the impact of CNS-directed treatment on child QoL, as well as sex and age at diagnosis as potential moderators. Methods Families of children with cancer (ages 5-17) were recruited at diagnosis or relapse (N = 336). Survivors completed the PedsQL at 3 (n = 96) and 5 years (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…While this may have resulted from too narrowly defining neurotoxicity, an underrepresentation of brain tumor survivors in our sample, or a sex by neurotoxicity interaction, 12 clinical attention to QoL may be beneficial for families regardless of neurotoxic treatment history.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…While this may have resulted from too narrowly defining neurotoxicity, an underrepresentation of brain tumor survivors in our sample, or a sex by neurotoxicity interaction, 12 clinical attention to QoL may be beneficial for families regardless of neurotoxic treatment history.…”
Section: Discussionmentioning
confidence: 96%
“…27 Among our sample, attrition at the 5-year follow-up was due to passive declines (i.e., unreachable), relocation, discontinued interest, and child death (n = 59). 12 Survivors (n = 100), mothers (n = 127), and fathers (n = 59) with data from the 5-year follow-up stress measure were included in analyses. Caregiverreported demographics are in Table 1, including a report of race and ethnicity in accordance with the U.S. Census.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between sex and QoL in pediatric patients with brain tumors remains controversial (Bell et al, 2018). Previous reports indicated that males had lower school-related QoL score (Bhat et al, 2005;Lipak et al, 2022;Ljungman et al, 2022). However, there were also reports that women had poorer QoL scores than men, or that no significant difference existed between males and females (Bull et al, 2014;Barrera et al, 2017;Quast et al, 2018).…”
Section: Discussionmentioning
confidence: 99%